2018
DOI: 10.5194/nhess-18-1969-2018
|View full text |Cite
|
Sign up to set email alerts
|

A study of earthquake recurrence based on a one-body spring-slider model in the presence of thermal-pressurized slip-weakening friction and viscosity

Jeen-Hwa Wang

Abstract: Earthquake recurrence is studied from the temporal variation in slip through numerical simulations based on the normalized form of equation of motion of a one-body spring-slider model with thermal-pressurized slip-weakening friction and viscosity. The wear process, whose effect is included in the friction law, is also taken into account in this study. The main parameters are the normalized characteristic displacement, U c , of the friction law and the normalized damping coefficient (to represent viscosity), η.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…Numerous factors, including wear process, friction, plasticity, strain rate etc., can influence the pattern of earthquake occurrence. Wear process (Wang 2018b) and time-strengthening static friction (Wang 2020) on a fault are two major factors in influencing the pattern of earthquake recurrence.…”
Section: Very-long-term Prediction: Earthquake Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous factors, including wear process, friction, plasticity, strain rate etc., can influence the pattern of earthquake occurrence. Wear process (Wang 2018b) and time-strengthening static friction (Wang 2020) on a fault are two major factors in influencing the pattern of earthquake recurrence.…”
Section: Very-long-term Prediction: Earthquake Recurrencementioning
confidence: 99%
“…Up to date, this is still a difficult challenge for earthquake scientists, even though there have been some physical models (cf. Wang 2016Wang , 2017Wang , 2018bWang , 2020Wang , 2021 and cited references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The slip duration is almost the rise time at a point on the source area. Wang (2018b) showed that the rise time increases with a decrease in the characteristic slip distance of a frictional law and an increases in either viscosity or inertia of fault-zone materials. The thickness of heated layer can affect the viscous stress.…”
Section: The Heat Flux Problemmentioning
confidence: 99%
“…For the perfect periodic model, the width, w, of a fault zone must be constant. In fact, numerous factors, including wear process, plasticity, strain rate etc., can change the value of w and thus influence the type of earthquake occurrence (see Wang 2018b). Wang (2018a) studied the effect of wear process in the fault zone on earthquake recurrence.…”
Section: The Earthquake Recurrence Problemmentioning
confidence: 99%
See 1 more Smart Citation